Ghanaian fathers' experiences of caring for preterm infants; a journey of exclusion. Issue 6 (December 2017) - Adama, Esther Abena; Sundin, Deborah; Bayes, Sara
Abstract: Aim: To explore Ghanaian fathers' experiences of caring for preterm infants in the neonatal unit and after discharge. Method: Participants were part of a larger study to explore parents' experiences of caring for preterm infants after discharge. Narrative inquiry methodology was used to interview nine fathers of preterm infants of gestational age 26–36 weeks at three stages-one week, one month and four months-after discharge from four level II and III neonatal units in Ghana. Data was analysed using thematic analysis guided by the three-dimensional narrative inquiry space. Ethical approval and consent from fathers were obtained before interviewing them at their residence. Result: Three themes emerged from the data showing the chronological journey of fathers from the neonatal unit till four months after discharge–1. In the neonatal unit – "there's no room for me; 2. Pre-discharge preparation – "I was not involved in discharge education" and 3. Home care/post discharge – "I'm scared of my preterm infant". Fathers reported being continuously excluded from the care of their preterm infants. This exclusion resulted in increased stress and lack of confidence in caring for their preterm infants after discharge. Conclusion: Fathers' experiences of caring for preterm infants is a journey characterized by exclusion and lack of caring confidence after discharge. Recognising and addressing the needs of fathers of preterm infants in the neonatal unit is essential in building their caring confidence after discharge.